2015
DOI: 10.3138/cpp.2014-079
|View full text |Cite
|
Sign up to set email alerts
|

Welfare States and Health Inequalities

Abstract: While much research points to the importance of a range of welfare state policies to reduce inequalities in health, the growing literature in this field is full of mixed and contradictory results. In this paper, we provide a brief discussion about the different conceptual and methodological approaches used in comparative research on the relationship between welfare policies and health. Against a theoretical discussion of possible linkages among one central welfare policy, unemployment benefit schemes, and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Other subjective and objective measures of health (e.g., adult and infant mortality rates or prevalence of specific conditions) should be considered for future cross-national research. We also limited our analysis to welfare effort, as measured by spending levels, and did not examine institutional measures of specific social policies and programs, another method of conceptualizing the welfare state that may provide a more comprehensive assessment of welfare state influence on health (Bergqvist et al 2013; Lundberg et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other subjective and objective measures of health (e.g., adult and infant mortality rates or prevalence of specific conditions) should be considered for future cross-national research. We also limited our analysis to welfare effort, as measured by spending levels, and did not examine institutional measures of specific social policies and programs, another method of conceptualizing the welfare state that may provide a more comprehensive assessment of welfare state influence on health (Bergqvist et al 2013; Lundberg et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Health researchers have already paid considerable attention to how the politics and policies of the welfare state play a role in distributing both overall health and inequalities in health across contexts. Welfare state effort has been linked to better population health (Brennenstuhl, Quesnel-Vallée, and McDonough 2012;Chung and Muntaner 2006;Conley and Springer 2001;Lundberg et al 2008), but research on the association between welfare state effort and health inequalities is less conclusive (Bambra and Eikemo 2009;Eikemo, Huisman, et al 2008;Lundberg et al 2015), with little attention paid to the relationship between welfare spending and inequalities based on minority status. Although minority groups are often overrepresented in the economically vulnerable populations that typically benefit from welfare effort, there is not enough evidence to conclude whether or how such policies affect the distribution of minority health outcomes.…”
mentioning
confidence: 99%
“…Both objects of study might differ in the way in which they affect health. Previous studies indicated that the focus on specific social policies could be the crux of the matter, compared to the study the welfare regimes (Beckfield and Bambra, 2016; Burstrom et al, 2010; Lundberg et al, 2015). In their review of 33 studies on health, health inequalities and welfare regimes, Brennenstuhl et al (2012: 399) concluded that ‘results were more consistent among the studies that examined policy instruments’.…”
Section: Introductionmentioning
confidence: 99%
“…The goal is to assess whether minimum income protection (MIP) accounts for the variations in the extent of health inequalities across Europe. To date, research has focused on policies for single mothers, family, old-age and unemployment policies (Burstrom et al, 2010; Ferrarini and Norström, 2010; Lundberg et al, 2008, 2015; Rodriguez, 2001), while minimum income protection has received only minimal attention despite its fundamental relevance to poverty and income-related inequalities (Bahle et al, 2011; Nelson, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation